Types and frequency of laboratory errors in Sawanpracharak hospital, Nakornsawan province: One year after laboratory accreditation - Pakasit Pratoomtone (Journal of Associated Medical Sciences, 2010)
Since  laboratory  tests  provide  essential  information  for  physicians  to  make  medical  decisions  for diagnosis, treatment and monitoring of the patient’s condition, we evaluated the types and frequency of errors in our  in-patient  department  of  clinical  pathology  laboratory  during  Mar  2008-February  2009  after  laboratory accreditation. Among a total of 314,400 specimens, we identified 2,720 errors, a relative frequency of 0.86% or 1 in 116 samples.  The  distribution  errors  were  pre-analytical  phase  86.76%,  analytical  phase  5.33%,  and post-analytical phase 7.90%. Most of pre-analytical errors were subjected to transcription in writing requests and inappropriate specimen collection, respectively. Although the errors did not cause any impact on patient safety, the samples may need to be collected again to repeat analysis, inconvenient for the patient, delaying treatment and increasing the cost. These data were valuable for more concerning in develop and improve standard operation procedure in order to prevent any errors that may occur.  Bull Chiang Mai Assoc Med Sci 2010; 43: 70-76.